Influence of Gender Characteristic on Transformation of The Adult Identity - KRASOVSKAIA, NATALIIA R. (The journal of contemporary issues in business and government, 2021)
The article presents the results of an empirical study aimed at identifying the influence of gender characteristics on transformation of the adult identity. It was revealed that identity is directly connected with gender characteristics of personality. It was found that gender characteristics, as well as sex, age, marital status and education have the most profound impact on the specificity of the transformation of adult identity. Criteria and specificity of crisis identity of the adult personality are considered. Criteria and specifics of the crisis identity of an adult are also examined.